2021
DOI: 10.3390/molecules26165001
|View full text |Cite
|
Sign up to set email alerts
|

The Nrf2 Pathway in Ischemic Stroke: A Review

Abstract: Ischemic stroke, characterized by the sudden loss of blood flow in specific area(s) of the brain, is the leading cause of permanent disability and is among the leading causes of death worldwide. The only approved pharmacological treatment for acute ischemic stroke (intravenous thrombolysis with recombinant tissue plasminogen activator) has significant clinical limitations and does not consider the complex set of events taking place after the onset of ischemic stroke (ischemic cascade), which is characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 290 publications
(302 reference statements)
0
54
0
Order By: Relevance
“…There are some limitations to this study. Under stress conditions (excessive accumulation of ROS and inflammatory stress), Nrf2-Keap1 interaction is disrupted, and Nrf2 translocates into the nucleus encoding proteins (i.e., HO-1) that counterbalance impairments in inflammatory and redox control [ 55 ]. Therefore, it would be more helpful to confirm Nrf2 is mediating these vascular protective effects if nuclear translocation of Nrf2 was also accessed.…”
Section: Discussionmentioning
confidence: 99%
“…There are some limitations to this study. Under stress conditions (excessive accumulation of ROS and inflammatory stress), Nrf2-Keap1 interaction is disrupted, and Nrf2 translocates into the nucleus encoding proteins (i.e., HO-1) that counterbalance impairments in inflammatory and redox control [ 55 ]. Therefore, it would be more helpful to confirm Nrf2 is mediating these vascular protective effects if nuclear translocation of Nrf2 was also accessed.…”
Section: Discussionmentioning
confidence: 99%
“…The increased levels of oxidation lead to the activation of nuclear factor–erythroid factor 2-related factor (Nrf-2) [ 43 ], an important transcription factor involved in the cellular response to oxidative stress. Ischemic stroke also results in oxidative stress and increased levels of Nrf-2 [ 44 ]. In our previous study, we showed that supplementation with B vitamins, including vitamin B12, results in increased levels of Nrf-2 and superoxide dismutase 2 (SOD2) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased levels of oxidation lead to the activation of nuclear factor-erythroid factor 2-related factor (Nrf-2) (An et al, 2021), an important transcription factor involved in cellular response to oxidative stress. Ischemic stroke also results in oxidative stress and increased levels of Nrf-2 (Farina et al, 2021). In our previous study, we showed that supplementation with B vitamins, including vitamin B12, results in increased levels of Nrf-2 and superoxide dismutase 2 (SOD2) (Jadavji et al, 2017).…”
Section: Discussionmentioning
confidence: 99%